Observation of the Z →ψ + - decay in pp collisions at s =13 TeV - Sirunyan, A.M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (American Physical Society, 2018)
This Letter presents the observation of the rare Z boson decay Z → ψlþl−. Here, ψ represents contributions from direct J=ψ and ψð2SÞ → J=ψX, lþl− is a pair of electrons or muons, and the J=ψ meson is detected via its decay to μþμ−. The sample of proton-proton collision data, collected by the CMS experiment at the LHC at a center-of-mass energy of 13 TeV, corresponds to an integrated luminosity of 35.9 fb−1. The signal is observed with a significance in excess of 5 standard deviations. After subtraction of the ψð2SÞ → J=ψX contribution, the ratio of the branching fraction of the exclusive decay Z → J=ψlþl− to the decay Z → μþμ−μþμ− within a fiducial phase space is measured to be BðZ → J=ψlþl−Þ= BðZ → μþμ−μþμ−Þ ¼ 0.67 0.18ðstatÞ 0.05ðsystÞ.